PATTERNS OF ADAPTATION OF RIVER BANKS COMMUNITIES IN FACING FLOOD DISASTER IN SOUTH KALIMANTAN - FAHRIANOOR; ANDIKA SANJAYA (CV KULTURA DIGITAL MEDIA, 2021)
South Kalimantan as an area that is blessed with a lot of river flows, this many river flows can be a blessing and can also be a disaster. As happened in January 2021, many districts in South Kalimantan were affected by floods. However, the people of South Kalimantan were able to deal with it and also minimal casualties, both in the form of property and life losses. The purpose of this study was to see the pattern of adaptation of the community in Tempakang Village and Halong Village in dealing with Floods. The results showed that the communication adaptation pattern of the riverbank community, in this case the village of Tampakang and the village of Halong, can be seen from the pattern of houses, namely houses on stilts. The adaptation process of the community in dealing with the flood disaster is closely related to the ability to predict the arrival of the rainy season which has an impact on flooding. Furthermore, the equipment and household furniture they have are generally made of light material so they are easy to move. In the village community of Tampakang, specifically accompanied by the ability to use boats and the ability to swim since childhood.